199 EMBEDDING PHYSICAL ACTIVITY WITHIN HOME CARE SERVICES FOR OLDER ADULTS IN IRELAND—A QUALITATIVE STUDY OF BARRIERS AND FACILITATORS. (18th November 2021) - Swan, L; Horgan, F; Cummins, V; Doyle, F; Galvin, R; Burton, E; Sorensen, J; Jabakhanji, S B; Skelton, D; Townley, B; Rooney, D; Jackson, G; et al.
Abstract: Background: In Ireland, over 53, 000 older adults are supported in their community by formal home support, amounting to an estimated 19 million care hours annually. There is a growing need to move beyond care, to more proactive approaches to maintain physical function. In a feasibility study, we delivered the 'Care to Move' (CTM) programme through existing home support services. The aim of the present qualitative study was to explore the experience and perceptions of Health Care Assistants (HCAs), who were trained in, and delivered the CTM programme. Methods: We conducted semi-structured telephone interviews with 22 HCAs involved in the delivery of the programme among older adults [n = 35, mean age 82.8 (7.8) years]. Interview transcripts were coded and analysed thematically to capture barriers and facilitators to programme delivery. Results: Barriers and facilitators were identified under three main themes i) the programme ii) the care setting, iii) the clients. Overall, there was a positive perception of the programme's focus on 'movement prompts and motivators', the 'fit' within home support services, and the training provided. Practical challenges of limited time and the task-orientation nature of home support were reported as recurring barriers for CTM. Many HCAs commented on the value and perceived positive benefits of the programme for their clients. Though negative perceptions of older adult's motivation or ability to engage with physical activity also emerged. Risk, such as injury or pain, was identified but was not a dominant theme. Conclusion: Our preliminary findings suggest that embedding physical activity initiatives within home support services could be feasible. Restructuring of services, engaging HCAs, and moving beyond traditional 'task-oriented' care models to more personalised proactive approaches may facilitate this initiative and support ageing in place.